A direct method-based strength evaluation of the cast aluminum beam used in a high-speed train. (October 2019) - Huang, Songhua; Xu, Yugong; Bezold, Alexander; Zhang, Lele; Chen, Geng; Broeckmann, Christoph
In this paper, the authors elaborate how numerical techniques developed from the direct method can be used to predict the load-bearing capacity of the aluminum casting beam structure which is presently used in the Chinese high-speed train CRH5A. The numerical method introduced in this paper is formulated based on the Melan's static theorem; thus, it determines the strength of the cast aluminum beam under both monotonic and cyclic loads without following the entire load profile. In addition to constructing the plastic and shakedown limits of the component, the proposed approach is also employed to study how stiffeners' thickness on the key areas influences the feasible load domains. Based on the intensive sensitivity analysis, an optimal thickness has been determined which gives the highest strength-to-weight ratio. To this end, the paper confirms that the direct method is a viable means for designing structures used in the rolling stock.